COMMUNITY EMPOWERMENT THROUGH COOKIE-MAKING TRAINING BASED ON LOCAL BANANAS AS A POTENTIAL BUSINESS PRODUCT ALTERNATIVE - Sachriani Sachriani; Mutiara Dahlia; Mariani Mariani; Wisnu Riyanto; Yuni Muliyana; Zahra Salindri (LPPM Univ. Ibn Khaldun Bogor, 2026)
Singasari Village, Jonggol District, Bogor Regency has abundant banana fruit potential; however, its utilization is still limited to fresh fruit, so it has not yet provided optimal economic added value for the community. This Community Service activity aims to improve the community's knowledge and skills in processing local bananas into Banana Sable Cookies as an alternative business product based on local food. The activity was carried out on 18 June 2026, involving 20 housewives through the stages of preparation, implementation, evaluation, and data analysis. Evaluation was conducted using pre-test, post-test, and a participant satisfaction questionnaire. The results showed an increase in the average pre-test score from 65 to 82 on the post-test, indicating an improvement in participants' understanding after the training. In addition, the satisfaction questionnaire results obtained an average score of 4,46, showing that participants gave a positive response to the material, learning media, delivery method, and implementation of the activity. This training not only improved participants' knowledge and skills in processing local bananas into value-added food products, but also increased participants' motivation to utilize local food potential as a home-based business opportunity. This activity is expected to support the community's economic empowerment while contributing to the achievement of the Sustainable Development Goals (SDGs), particularly No Poverty and Good Health and Well-being.